Solve (y-z/yz)p+(z-x/xy)q=x-y/yx
The given problem must be, "\\dfrac{y-z}{yz}p+\\dfrac{z-x}{xz}q=\\dfrac{x-y}{yx}" .
This problem can be written as, "x(y-z)p+y(z-x)q=z(x-y)".
The subsidiary equations are,
"\\dfrac{dx}{x(y-z)} = \\dfrac{dy}{y(z-x)} =\\dfrac{dz}{z(x-y)}"
Using the multipliers 1,1,1 each of the above ratio is equal to
"\\dfrac{dx+dy+dz}{x(y-z)+y(z-x)+z(x-y)}=\\dfrac{dx+dy+dz}{0}"
Hence,
"\\begin{aligned}\ndx+dy+dz&=0,\\\\ \\text{Integrating we get,}\\\\\nx+y+z&=c_{1}\n\\end{aligned}"
Using multipliers "\\frac{1}{x},\\frac{1}{y},\\frac{1}{z}" the ratio is equal to
"\\dfrac{\\frac{1}{x}dx+\\frac{1}{y}dy+\\frac{1}{z}dz}{(y-z)+(z-x)+(x-y)}=\\dfrac{\\frac{1}{x}dx+\\frac{1}{y}dy+\\frac{1}{z}dz}{0}"
Hence,
"\\begin{aligned}\n\\frac{1}{x}dx+\\frac{1}{y}dy+\\frac{1}{z}dz&=0\\\\ \\text{Integrating we get,}\\\\\n\\ln x+\\ln y+\\ln z&=\\ln c_{2}\\\\\n\\ln (xyz)&=\\ln c_{2}\\\\\nxyz&=c_{2}\n\\end{aligned}"
Thus, the general solution is
"\\begin{aligned}\n\\phi(c_{1},c_{2})&=0\\\\\n\\phi(x+y+z,xyz)&=0\n\\end{aligned}"
Comments
Leave a comment